Nilai Sosial dan Budaya Tradisi Menyilaq Masyarakat Suku Sasak di Desa Jerowaru - Paenal Juni Harian; Syafruddin Syafruddin; Imam Malik (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to analyze the social and cultural values embedded in the menyilaq tradition in Jerowaru Village, East Lombok Regency. The menyilaq tradition is a practice of direct invitation that is still preserved as part of local wisdom and serves as a social system that strengthens community bonds. This study employs a qualitative approach using ethnographic methods. Data collection was conducted through non-participant observation, semi-structured in-depth interviews, and documentation, involving subjects from the ranks of pemesilaq, epen gawe, and the community being invited, as well as informants comprising traditional leaders and Sasak cultural figures. The research findings indicate that the menyilaq tradition embodies social and cultural values such as responsibility, sukerede, sangkep, tate krame, serembat angen, besiru, and beriuk. This tradition also serves as an effective medium for interaction and socialization in maintaining community harmony and solidarity. Amidst the tide of modernization, the community of Jerowaru Village continues to uphold the tradition of menyilaq as a form of cultural resistance and an effort to preserve noble values. Thus, the tradition of menyilaq not only serves as a social ritual but also as a foundation for building a harmonious and sustainable social structure amidst the disruption of values caused by modernity. Kata Kunci: Menyilaq, Nilai Sosial, Nilai Budaya, Desa Jerowaru.